CCAFS WA informs the development of an investment framework for mobilization of resources into climate smart agriculture (CSA) in Ghana - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The Food and Agriculture Organization of the United Nations (FAO) in a bid to strengthen climate-smart agriculture (CSA) actions at the local level requested the Ghana CCAFS Science-policy dialogue platform to translate the National Climate-Smart Agriculture and Food Security Action Plan (2016-2020) developed under the auspices of CCAFS into a sub-national CSA investment framework to attract CSA funding (http://www.fao.org/3/i9470en/I9470EN.pdf).